Microstructure refinement of commercial 7xxx aluminium alloys solidified by the electromagnetic vibration technique - Li, M; Tamura, T; Omura, N; Murakami, Y; Tada, S (IOP conference series. Materials Science and Engineering, 2016)
This paper examines the microstructure refinement of commercial 7xxx aluminium alloys solidified by the electromagnetic vibration technique (EMV) as a function of vibration frequency, f. The microstructure evolution reveals that at the low frequency of f = 62.5 Hz, the solidified microstructure is coarse and with the increase of vibration frequency to f = 500 Hz, the grain size becomes the finest and further increase of frequency to f = 2000 Hz results in coarsening of microstructures. The refinement mechanism is clarified when considering the significant difference in electrical resistivities of the solid and the liquid in mushy zone, in which both phases coexist and subject to vibration. The frequency-dependent refinement behaviour is revealed when the displacement of the mobile solid and sluggish liquid is taken into account during solidification. In contrast to 3xxx aluminium alloys, no giant compounds have been discerned in the present 7xxx alloy regardless of the solidification condition. The formation of crystalline twin is briefly discussed when considering the vibration condition.